The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1104/pp.104.042978
|View full text |Cite
|
Sign up to set email alerts
|

A Complementary Bioinformatics Approach to Identify Potential Plant Cell Wall Glycosyltransferase-Encoding Genes  

Abstract: Plant cell wall (CW) synthesizing enzymes can be divided into the glycan (i.e. cellulose and callose) synthases, which are multimembrane spanning proteins located at the plasma membrane, and the glycosyltransferases (GTs), which are Golgi localized single membrane spanning proteins, believed to participate in the synthesis of hemicellulose, pectin, mannans, and various glycoproteins. At the Carbohydrate-Active enZYmes (CAZy) database where e.g. glucoside hydrolases and GTs are classified into gene families pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 55 publications
1
83
0
Order By: Relevance
“…This domain is highly conserved between KOBITO1 homologs in land plants and green algae but is not present in other organisms. While KOBITO1 is not part of CAZy, a database of carbohydrate active enzymes, a bioinformatics approach aimed at finding additional plant glycosyltransferase genes has identified KOBITO1 as one of 27 non-CAZy-classified putative glycosyltransferases (Egelund et al, 2004). Two genes out of this group of 27 have been proven to encode glycosyltransferases that function in pectin biosynthesis (Egelund et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This domain is highly conserved between KOBITO1 homologs in land plants and green algae but is not present in other organisms. While KOBITO1 is not part of CAZy, a database of carbohydrate active enzymes, a bioinformatics approach aimed at finding additional plant glycosyltransferase genes has identified KOBITO1 as one of 27 non-CAZy-classified putative glycosyltransferases (Egelund et al, 2004). Two genes out of this group of 27 have been proven to encode glycosyltransferases that function in pectin biosynthesis (Egelund et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that glycosyltransferase may act across plant species as a defense to very different pathogens. Glycosyltransferases also play a role in cell wall synthesis (Lao et al, 2003;Egelund et al, 2004) and may suggest a role in defense to RKN via this function. Research to better understand the role of this enzyme in RKN resistance is currently in progress.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental downregulation of this gene via virus-induced gene silencing (VIGS) restores susceptibility to M. incognita in 'Motelle,' indicating that this function is necessary for Mi-mediated resistance. Glycosyltransferases have been implicated in carbohydrate biosynthesis and associated in plant stress and defense responses (Dixon, 2001;Qi et al, 2005;Vogt and Jones, 2000) and cell wall synthesis (Egelund et al, 2004;Lao et al, 2003); this is the first report, to our knowledge, of a role for a glycosyltransferase in nematode resistance.…”
mentioning
confidence: 99%
“…Position of the predicted TMD is indicated by the line (dotted line for RGXT1 and solid line for RGXT2; Egelund et al, 2004), and the DxD motif involved in the binding of UDP-sugar is indicated with asterisks above the sequence alignment. 1 online).…”
Section: Rgxt1 and Rgxt2 Expressed In Baculovirus-transfected Insect mentioning
confidence: 99%
“…In addition, the very limited number of donor and especially acceptor substrates has further hampered the identification of novel plant CW GTs. As a significant proportion of Arabidopsis GTs probably remains to be classified, we developed a bioinformatic filtering strategy aimed at identifying unclassified CW GTs in Arabidopsis (Egelund et al, 2004). As a result, 27 putative GTs were identified, and two of these gave rise to a new family in CAZy (GT-family-77; Coutinho et al, 2003a; http://afmb.cnrs-mrs.fr/CAZY/).…”
Section: Gene Identification and Deduced Protein Structurementioning
confidence: 99%